2014
DOI: 10.32890/mjli.11.2014.7665
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Social Support as Predictor of University Adjustment and Academic Achievement Amongst First Year Undergraduates in a Malaysian Public University

Abstract: Purpose – This study was conducted to examine relationships between perceived social support, university adjustment and academic achievement of fi rst semester students enrolled in various undergraduate programs in a Malaysian public university.   Methodology – This study employed a quantitative approach with a descriptive correlation design to address the research objectives. The adapted version of the “Interpersonal Support Evaluation List” (1985) and the “Student Adaptation to College Questionnaire” (1999) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
4
13
1
Order By: Relevance
“…However, the correlational analysis found that college adjustment was not significantly related to academic performance. The current finding contradicts the previous study by Abdullah et al (2010). Although the latter finding suggests that academic adjustment significantly shapes college students' academic performance, the present study suggests otherwise.…”
Section: College Adjustment and Academic Performancecontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the correlational analysis found that college adjustment was not significantly related to academic performance. The current finding contradicts the previous study by Abdullah et al (2010). Although the latter finding suggests that academic adjustment significantly shapes college students' academic performance, the present study suggests otherwise.…”
Section: College Adjustment and Academic Performancecontrasting
confidence: 99%
“…College adjustment plays a significant role in academic performance. Previous studies found that students who were able to adjust with academic context had the better academic outcomes (Abdullah, Elias, Uli, & Mahyuddin, 2010). Academic adjustment, however, is not a fixed individuals' ability but a volatile and vulnerable to external factors.…”
Section: College Adjustment and Academic Performancementioning
confidence: 98%
“…The internal consistency (Cronbach’s α ) ranged between 0.75 and 0.84 for problem-focused coping and between 0.74 and 0.87 for emotion-focused coping in an investigation with university-related problems among North American, Germany and Malaysian students (Ahmoi-Essau and Trommsdorff, 1996). In another study Abdullah et al (2010) translated WoC into the Malay language and the content was validated by a panel of experts. The translated and adapted version of WoC used in this study was found to be reliable (Cronbach’s α =0.87 total, ranging from 0.54 to 0.79 for the eight subscales).…”
Section: Methodsmentioning
confidence: 99%
“…Perceived social support is one of the most important protecting factors against the disruptive or adverse experience of starting university [ 11 , 12 , 13 ]. Although some of the specific situations students face (remaining in their parents’ home, maintaining ties of friendship, etc.)…”
Section: Introductionmentioning
confidence: 99%